Effect of Teriflunomide on Cells From Patients With Human T-cell Lymphotropic Virus Type 1–Associated Neurologic Disease. Issue 3 (May 2021) - Enose-Akahata, Yoshimi; Ngouth, Nyater; Ohayon, Joan; Mandel, Matt; Chavin, Jeffrey; Turner, Timothy J.; Jacobson, Steven
Abstract : Objective: To test the hypothesis that teriflunomide can reduce ex vivo spontaneous proliferation of peripheral blood mononuclear cells (PBMCs) from patients with human T-cell lymphotropic virus type 1 (HTLV-1)–associated myelopathy/tropical spastic paraparesis (HAM/TSP). Methods: PBMCs from patients with HAM/TSP were cultured in the presence and absence of teriflunomide and assessed for cell viability, lymphocyte proliferation, activation markers, HTLV-1 tax and HTLV-1 hbz messenger ribonucleic acid (mRNA) expression, and HTLV-1 Tax protein expression. Results: In culture, teriflunomide did not affect cell viability. A concentration-dependent reduction in spontaneous proliferation of PBMCs was observed with 25 μM (38.3% inhibition), 50 μM (65.8% inhibition), and 100 μM (90.7% inhibition) teriflunomide. The inhibitory effects of teriflunomide were detected in both CD8 + and CD4 + T-cell subsets, which are involved in the immune response to HTLV-1 infection and the pathogenesis of HAM/TSP. There was no significant change in HTLV-1 proviral load (PVL) or tax mRNA/Tax protein expression in these short-term cultures, but there was a significant reduction of HTLV-1 PVL due to inhibition of proliferation of CD4 + T cells obtained from a subset of patients with HAM/TSP. Conclusions: These results suggest that teriflunomide inhibits abnormal T-cell proliferation associated with HTLV-1 infection and may have potential as a therapeutic option in patients with HAM/TSP.